1999
DOI: 10.1385/endo:11:1:23
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Receptor mRNA Expression in the Rhesus Monkey Ovary

Abstract: Immunocytochemical detection of androgen receptors (ARs) in several compartments of the macaque ovary, including the germinal epithelium, follicle, and corpus luteum, suggests a role for androgens in modulating ovarian function via the classical receptor-mediated pathway. To examine AR mRNA expression in the rhesus monkey ovary, total RNA was isolated from whole ovaries, the germinal epithelium-enriched cortical and medullary compartments of the ovary, and corpora lutea from early (d 3-5), mid (d 6-8), mid-lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 45 publications
3
14
0
Order By: Relevance
“…AR mRNA is present in primate corpora lutea (CL) (Duffy et al 1999). During the early luteal phase of a cycle, developing and even regressing primate CL exhibit AR immunostaining (Hild-Petito et al 1991).…”
Section: Ar Expression In Corpora Luteamentioning
confidence: 99%
“…AR mRNA is present in primate corpora lutea (CL) (Duffy et al 1999). During the early luteal phase of a cycle, developing and even regressing primate CL exhibit AR immunostaining (Hild-Petito et al 1991).…”
Section: Ar Expression In Corpora Luteamentioning
confidence: 99%
“…Studies across species reported that ARs are expressed in theca cells, granulosa cells (GCs), and the oocyte of the follicle and throughout most stages of follicular development (Horie et al 1992, Chadha et al 1994, Hirai et al 1994, Suzuki et al 1994, Tetsuka & Hillier 1996, Szoltys & Slomczynska 2000, Slomczynska & Tabarowski 2001, Gill et al 2004, Hampton et al 2004, Juengel et al 2006. However, their expression patterns may differ between ovarian cell types (Tetsuka & Hillier 1996, Szoltys & Slomczynska 2000 and in most species, AR is abundant in the preantral/antral stages of follicular development but declines as follicles mature to the preovulatory stage (Horie et al 1992, Chadha et al 1994, Suzuki et al 1994, Duffy et al 1999, Hampton et al 2004, Juengel et al 2006. In fact, AR is expressed in cell-specific regions of human ovarian follicles at all stages of follicular development beyond the primordial phase (Rice et al 2007).…”
Section: Ar Expression and Regulationmentioning
confidence: 99%
“…Serum estradiol and P 4 levels were determined using ELISA (Elecsys 2010; Roche Diagnostics, Indianapolis, IN) as described previously [18]. The first day of low (Ͻ100 pg/ml) serum estradiol levels following the midcycle estradiol peak corresponds with the day after the LH surge and, therefore, was considered to be Day 1 of the luteal phase [19].…”
Section: Animal Protocols and Tissuesmentioning
confidence: 99%